Evaluating LMS-Based Extensive Reading Activities’ Impact on Islamic Undergraduate Non-English Majors’ Comprehension and Engagement - Hidayati, Dewi; Utami, Prastyo Rinie Budi (Nexus Publishing NXP, 2025)
Extensive reading (ER) is widely recognized for improving reading comprehension and engagement; however, research on its effectiveness within Learning Management System (LMS)-based instruction for Islamic undergraduate students in non-English departments remains limited. Many first-year students at STAI Diponegoro Tulungagung, Indonesia, struggle with academic reading due to limited vocabulary exposure, lack of motivation, and inadequate reading strategies. To address this gap, this study investigates the effectiveness of LMS-based extensive reading activities in enhancing reading comprehension and engagement among non-English major Islamic undergraduate students. Employing a sequential mixed-methods approach, the study involved 35 first-semester students participating in an ER program integrated into an LMS. Data were collected through pre- and post-tests to assess reading comprehension progress and a closed-ended questionnaire measuring engagement across key dimensions: motivation, reading strategies, and perceived challenges. Findings indicate that LMS-based ER activities enhanced students’ comprehension, particularly in identifying main ideas and contextual meaning inference, supporting the role of structured digital reading tasks. Participants reported increased motivation and engagement, particularly due to the accessibility of materials, self-paced learning, and interactive LMS features. However, some students struggled with content overload, digital distractions, and difficulties in sustaining motivation without direct instructor intervention. Additionally, technical challenges such as internet instability and limited LMS familiarity hindered some students’ experiences. The study underscores the benefits and challenges of LMS-based ER for non-English major Islamic students, highlighting the need for adaptive support to sustain engagement and reading proficiency. Future research should focus on long-term implementation and instructional enhancements for optimized digital ER.